An Analysis of Window Dressing Practices in ASEAN Healthcare Companies in 2023 - Liliek Nur Sulistiyowati; Ririh Anggraini Setyahety; Sintiya Oktavia Salsabila (Universitas Bina Sarana Informatika, 2026)
Window dressing practices have become a significant phenomenon in the ASEAN healthcare sector following the COVID-19 pandemic, particularly in 2023. Uncertainty in financial reporting and pressure to demonstrate positive performance have driven management to employ manipulation strategies, including cash management, leverage, and increased liquidity ratios, toward the end of the reporting period. The healthcare sector, with its high capital requirements and strict regulations, has the potential to influence investor decisions and market stability. This study employed an associative quantitative approach, targeting healthcare companies in Indonesia, Malaysia, Thailand, and Vietnam. The population was 90 companies, with purposive sampling as the data collection technique, resulting in a sample of 55 companies. Quarterly financial data for 2023 were collected from public reports and analyzed using multiple regression analysis with SPSS version 25. The results indicate that cash holdings and leverage significantly influence window dressing practices, while company size and managerial ownership vary across countries. Increased liquidity ratios at the end of the reporting period reinforce the indication of year-end effects. Differences in financial structures and characteristics of ASEAN capital markets result in different practice patterns across countries. These findings expand the earnings management literature and provide practical implications for investors and regulators in improving transparency, oversight, and harmonizing capital market policies across countries.